Collagen Scaffolds with Controlled Insulin Release and Controlled Pore Structure for Cartilage Tissue Engineering. (25th February 2014) - Nanda, Himansu Sekhar; Chen, Shangwu; Zhang, Qin; Kawazoe, Naoki; Chen, Guoping
Abstract : Controlled and local release of growth factors and nutrients from porous scaffolds is important for maintenance of cell survival, proliferation, and promotion of tissue regeneration. The purpose of the present research was to design a controlled release porous collagen-microbead hybrid scaffold with controlled pore structure capable of releasing insulin for application to cartilage tissue regeneration. Collagen-microbead hybrid scaffold was prepared by hybridization of insulin loaded PLGA microbeads with collagen using a freeze-drying technique. The pore structure of the hybrid scaffold was controlled by using preprepared ice particulates having a diameter range of 150–250  μ m. Hybrid scaffold had a controlled pore structure with pore size equivalent to ice particulates and good interconnection. The microbeads showed an even spatial distribution throughout the pore walls. In vitro insulin release profile from the hybrid scaffold exhibited a zero order release kinetics up to a period of 4 weeks without initial burst release. Culture of bovine articular chondrocytes in the hybrid scaffold demonstrated high bioactivity of the released insulin. The hybrid scaffold facilitated cell seeding and spatial cell distribution and promoted cell proliferation.